Information systems plant food commodities district Coal-based web using php and mysql - Justira Mai Nora Siregar; Acwil Putra Munir; Saipul Bahri Daulay (Universitas Sumatera Utara, 2013)
Food corps information system in Batu Bara Regency are still stored in books and/or files that are very limited in effectiveness. Computerized information delivery methods and internet networks are solutions that are worth to try to overcome the problems of information flow. Study was designed to produce systems that can help process the delivering, storing, and monitoring of data displayed in a web form. The systems were designed in a user oriented programming language PHP, and MySQL database web Apache webserver. This system could improve efficiency and effectiveness of information flow, especially food corps information. The results showed that the distribution and types of food corps commodities in each district in Batu Bara Regency was different. The spread and the kind depend on topographic, the price level and market demand in the area.